Cognitive Deficits in Schizophrenia Patients and Their First-Degree Relatives: A Comparative Analysis - Kelkar, Amol (Journal of Biomedical and Pharmaceutical Research, 2020)
Background: Schizophrenia is associated with severe cognitive impairments, including deficits in memory, attention, and executive function. These cognitive deficits are also observed in first-degree relatives of individuals with schizophrenia, suggesting a potential genetic or familial predisposition. Understanding these cognitive impairments in both patients and their relatives can provide valuable insights into the hereditary aspects of the disorder and aid in early identification and intervention. Aim: To compare neurocognitive deficits in patients with schizophrenia and their first-degree relatives, and to assess the potential hereditary patterns of these cognitive impairments. Material and Methods: A total of 60 participants, including 30 patients with schizophrenia and 30 first-degree relatives, were assessed using standardized neuropsychological tests. Data on memory, attention, and executive function were collected and analyzed. Results: Patients with schizophrenia exhibited more pronounced cognitive deficits compared to their relatives. Significant correlations were found between cognitive impairments and the risk of developing schizophrenia. Conclusion: Schizophrenia patients show more severe cognitive deficits than their first-degree relatives, highlighting potential early markers for the disorder and the need for targeted interventions. Keywords: Schizophrenia, neurocognitive deficits, first-degree relatives, cognitive impairments, memory, attention, executive function, genetic predisposition, psychiatric disorders and early intervention.